Uniqueness of a 3-D coefficient inverse scattering problem without the phase information. (18th August 2017) - Klibanov, Michael V; Romanov, Vladimir G
Abstract: We use a new method to prove the uniqueness theorem for a coefficient inverse scattering problem without the phase information for the 3-D Helmholtz equation. We consider the case when only the modulus of the scattered wave field is measured and the phase is not measured. The spatially distributed refractive index is the subject of interest in this problem. Applications of this problem are in imaging of nanostructures and biological cells.